MENINGKATKAN KEMAMPUAN KOGNITIF BERHITUNG MELALUI MEDIA DAKON DI TK AS-SHOLIHIN SURABAYA TAHUN AJARAN 2022/2023 - ISTIFADAH, IFFAH (Universitas Narotama, 2024)
The background of this research is the low ability to recognize students' geometric shapes because the method used does not motivate and encourage children. This causes students to get bored in learning because the learning process in class tends to wait and children still feel shy in expressing opinions. This study aims to determine dakon media as a tool to facilitate arithmetic in Kindergarten B children. The method used is quantitative descriptive. Observations were made three times. The subjects of this study were As-Sholihin PAUD students, Keputih Village, Sukolilo District, Surabaya City for the 2022/2023 academic year with a total of 20 students. The results obtained from research based on pre-cycle observation data obtained an average learning mastery of 25% or as many as 5 children. In the first cycle, students' understanding of learning increased with mastery learning reaching an average of 45% or as many as 9 children. Getting the percentage of learning completeness in cycle II increased by 85% or as many as 17 children. So it can be concluded that the use of the demonstration method through dakon media can improve numeracy skills in As-Sholihin PAUD Keputih Village, Sukolilo District, Surabaya City for the 2022/2023 school year. Finally, the researcher suggests that teachers to improve their numeracy skills should use the demonstration method through dakon media. Keywords: Improving, counting, dakon media